A REVIEW OF HUMAN CAPITAL MANAGEMENT PRACTICES FOR ENHANCING WORKFORCE AGILITY AND KNOWLEDGE SHARING - Arnold AF Sihombing; Dhenny Asmarazisa; Catur Fatchu Ukhriyawati (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
In an increasingly dynamic and knowledge-driven business environment, organizations must develop agile workforces and effective knowledge-sharing mechanisms to sustain competitiveness. This study reviews and synthesizes human capital management (HCM) practices that enhance workforce agility and facilitate knowledge exchange. Drawing on a systematic and narrative literature review of academic studies, industry reports, and case evidence, the paper identifies key practices such as flexible work arrangements, continuous learning and skill development, agile performance management, collaborative cultures, incentive systems, and technology-enabled knowledge platforms. The findings highlight that workforce agility and knowledge sharing are interdependent capabilities that reinforce each other through cross-functional collaboration and learning-oriented organizational structures. The study also examines critical enablers, including organizational culture, leadership support, and technological infrastructure, as well as barriers such as resistance to change and structural rigidity. A conceptual framework is proposed to explain how HCM practices influence agility and knowledge-sharing processes, ultimately leading to improved innovation, performance, and organizational resilience. The review contributes to the HRM and knowledge management literature by integrating these domains into a unified perspective. It concludes that organizations must adopt flexible, learning-driven, and technology-supported HCM strategies to build adaptive and knowledge-rich workforces.